THE INFLUENCE OF RELIGIOSITY AND HALAL LABELING ON THE PURCHASE DECISIONS OF PACKAGED FOOD PRODUCTS - Risma, Risma; Rusdiana; Lisda Aisyah (Journal of Management and Islamic Finance, 2024)
This research aims to investigate consumer perceptions and behavior towards halal labels. Religiosity has a significant impact on various aspects of life, such as cultural beliefs and human behavior. This research is field research with a quantitative approach. Namely the type of research used to test theories through research variables and analyze data using statistical procedures. The sample used in this research was 98 people from the village of Tanjung Rema Martapura, Banjar Regency. The results of this research show that can be interpreted that the halal label and religiosity have a significant influence and has been proven to have a partial effect on purchasing decisions. The halal label has a more significant impact on purchasing decisions than religiosity due to reasons related to trust, convenience, and clarity in the offered product. The halal label provides clear assurance to consumers, as products with this label have gone through a certification process that ensures adherence to cleanliness, safety, and quality standards. This differs from religiosity, which is more subjective and tends to vary among individuals.